1985
DOI: 10.1177/104649648501600406
|View full text |Cite
|
Sign up to set email alerts
|

Pregroup Training

Abstract: Earlier reviews have asserted the superiority of structure versus ambiguity in the practice of group therapy. This review attempts to specify the dimensions that lead to this asserted superiority. The pregroup training literature is reviewed in terms of method and timing of presentation and content of training. A model is proposed that links content and timing with issues in group development Implications for practice and research are noted.The comparative effectiveness of structure versus ambiguity in the pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Two factors that may be related to the impact of the intervention are the duration of individuals’ membership in the group and their trait self-esteem levels. A number of studies have found that members’ reactions to group therapy depend, in part, on how long they have participated in the group (Bednar & Kaul, 1994; Corazzini & Heppner, 1981; Corazzini, Heppner, & Young, 1980; Fuhriman & Burlingame, 1990; Kivlighan, Corazzini, & McGovern, 1985; Kivlighan, Jauquet, Hardie, Francis, & Hershberger, 1993). Kivlighan, McGovern, and Corazzini (1984), drawing on Tuckman’s (1965)stage theory, demonstrated that matching the content and timing of training interventions is crucial for a successful outcome.…”
mentioning
confidence: 99%
“…Two factors that may be related to the impact of the intervention are the duration of individuals’ membership in the group and their trait self-esteem levels. A number of studies have found that members’ reactions to group therapy depend, in part, on how long they have participated in the group (Bednar & Kaul, 1994; Corazzini & Heppner, 1981; Corazzini, Heppner, & Young, 1980; Fuhriman & Burlingame, 1990; Kivlighan, Corazzini, & McGovern, 1985; Kivlighan, Jauquet, Hardie, Francis, & Hershberger, 1993). Kivlighan, McGovern, and Corazzini (1984), drawing on Tuckman’s (1965)stage theory, demonstrated that matching the content and timing of training interventions is crucial for a successful outcome.…”
mentioning
confidence: 99%
“…For the purposes of this study, RI will hereafter be used to denote any procedure designed to educate the client about the process of therapy. Most of the research attention has focused generally on “outcome,” which often included a focus on process measures, and has indicated that, overall, RI procedures produce significant positive effects (see Bednar, Weet, Evensen, Lanier and Melnick, 1974; Heitler, 1976; LaTorre, 1977; and Orlinsky & Howard, 1986, for reviews focusing on the effects of preparatory training for individual therapy and Kivlighan, Corazzini, & McGovern, 1985; Mayerson, 1984, for reviews focusing on the effects of preparatory training for group therapy, respectively). Fewer studies (e.g., Garrison, 1978; Warren & Rice, 1972) have been conducted using premature termination as a dependent variable in general outpatient psychotherapy, and have provided mixed results.…”
Section: A Brief History Of Preparatory Education For Therapymentioning
confidence: 99%
“…Multiple methods of training, particularly interactive ones (videotapes with discussion, practice sessions, etc. ), are most effective (Kivlighan, Corazzini, & McGovern, 1985). Training procedures usually consist of individual sessions emphasizing the safe and supportive qualities of a group, basic education about group roles and process, the benefits of self-disclosure, interpersonal feedback, here-and-now interactions, therapeutic factors, and realistic prognostic expectations.…”
Section: The Hybrid Group Modelmentioning
confidence: 99%